The management of parking facilities in shopping complex case study: Mid Valley Megamall and Pertama Complex / Siti Hajar Shaikh Abdullah - Shaikh Abdullah, Siti Hajar (2010)
The growth of the economic had influenced the numbers of buildings in Klang Valley area, there are plenty of commercial building, residential and special properties. The shopping complexes in Klang Valley are competing with each others, thus the management have to upgrade the facilities at the mall to attract the customers and investors besides generating more incomes. Due to the growth of the economic, the numbers of population who own and use motor vehicles in their daily activities have increased the demand for vehicle parking space. The management of the shopping complex is taking the initiatives by managing and maintaining the parking space to provide to the customers or visitors. The facility or property management of the shopping complex is responsible to carry out works to take care the facilities inside the building and outside at required standards. Property and facility management can creates business opportunities, improve business relation but most of all it generates significant business returns. This research will focus on the facilities in the parking space at Mid Valley Megamall and Pertama Complex which are function to give pleasure to the visitors or customers. Based to the research, the findings showed that the facilities equipped at the parking space of Mid Valley Megamall are better compare to Pertama Complex for example better signage, security and cleanliness. However, there are problems incurred in relation with the facilities at the parking space for example inadequate parking bays for the customers at Mid Valley Megamall and maintenance problems at Pertama Complex. The management of the shopping complex should immediately take action for example more supervision and monitoring towards their workers and facilities to overcome the problem and to maintain their tenants, investors and most importantly the customers.